2019
DOI: 10.22146/ijeis.38729
|View full text |Cite
|
Sign up to set email alerts
|

Pengenalan Karakter Tulisan Tangan Dengan K-Support Vector Nearest Neighbor

Abstract: AbstrakKarakter pada tulisan tangan cukup sulit untuk dikenali dengan mesin karena setiap orang memiliki gaya penulisan yang berbeda-beda. Penelitian ini mengenali pola karakter angka dan huruf pada tulisan tangan dengan memanfaatkan algoritma klasifikasi K-Nearest Neighbor (KNN). Proses pengenalan tulisan tangan dilakukan dengan mempraproses citra tulisan tangan, melakukan segmentasi untuk mendapatkan karakter tunggal dari sekumpulan karakter pada citra, ekstraksi ciri untuk mendapatkan fitur, dan klasifikas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…2b), the absorption band showing Brønsted acid site reappeared after impregnation with Ni metal. The characterization results show that the IR spectra could hardly give a clear indication of the presence of zirconium oxide as a pillar within the interlayer of bentonite [8].…”
Section: X-ray Fluorosence Analysismentioning
confidence: 92%
See 3 more Smart Citations
“…2b), the absorption band showing Brønsted acid site reappeared after impregnation with Ni metal. The characterization results show that the IR spectra could hardly give a clear indication of the presence of zirconium oxide as a pillar within the interlayer of bentonite [8].…”
Section: X-ray Fluorosence Analysismentioning
confidence: 92%
“…In previous study, it was found that the clay samples used were montmorillonite minerals with typical peaks in d 001 at 2θ = 5.29º (d = 16.69 Å) [8]. The typical peak of montmorillonite is still visible but has shifted to angle 2θ smaller than 5º.…”
Section: X-ray Fluorosence Analysismentioning
confidence: 93%
See 2 more Smart Citations
“…Tahap ini adalah tahap untuk menemukan dan memperbaiki kualitas citra judul buku TGA. Citra asli berupa citra berwarna diubah menjadi citra gray [11] dengan persamaan (1). Gray=0.2989xR+0.5870xG+0.1140xB…”
Section: Preprocessingunclassified